2018
DOI: 10.1002/ecs2.2274
|View full text |Cite
|
Sign up to set email alerts
|

Life history and habitat explain variation among insect pest populations subject to global change

Abstract: Population dynamic responses to global change have varied widely among taxa. Most studies of population dynamics of insect pests focus on one or a few species, leaving open the question of whether changes in outbreak patterns are species‐specific or reveal predictable responses to global change, and what factors explain differences among populations. We analyzed 64 multi‐decadal time series of agricultural and forest pest insect populations in the United States. We first characterized populations according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 71 publications
1
21
0
3
Order By: Relevance
“…geographical space) to be represented as the sum of many sine waves of different frequency. In a similar fashion, temporal patterns in pest populations were characterized using a combination of wavelet analyses and autoregressive moving-average model fitting (Walter et al 2018). The wavelet and spectral analyses estimate the amount of variation in a time series attributable to a particular frequency (scale) at a particular point in time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…geographical space) to be represented as the sum of many sine waves of different frequency. In a similar fashion, temporal patterns in pest populations were characterized using a combination of wavelet analyses and autoregressive moving-average model fitting (Walter et al 2018). The wavelet and spectral analyses estimate the amount of variation in a time series attributable to a particular frequency (scale) at a particular point in time.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a 14-yr time series of moth light trap data from an alder carr undisturbed forest (where no successional trends were expected), both positive and negative trends were found in many more species than expected by chance (Lepš et al 1998). Similarly, in analyses of various time series of agricultural and forest pest insect populations in the United States Walter et al (2018) found that half of the time series exhibited a long-term trend. Thus, synchrony values can also be affected by these trends.…”
Section: Introductionmentioning
confidence: 95%
“…Because synchronous local patterns are amplified in the area‐wide total (Schindler et al ., ), these synchronous fluctuations can manifest as intermittent or periodic outbreaks, particularly for relatively abundant species like corn earworm, true armyworm, and forage looper. State‐wide population fluctuations of beet armyworm, celery looper, corn earworm, dingy cutworm, and forage looper were characterised as cyclic in a separate analysis (Walter et al ., ), and spatial synchrony probably magnifies the negative impacts of cyclic outbreaks. Although its overall abundance declined, due in part to the introduction of Bt corn (Bohnenblust et al ., ), corn earworm remained relatively abundant throughout the study period, and its populations have become increasingly synchronous since the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Climate and weather, by which we distinguish between, respectively, long‐term and short‐term changes in atmospheric conditions, have long been recognised as important factors regulating insect populations (Andrewartha and Birch ), and in recent decades concerns have emerged that climate change may increase the frequency and severity of damaging insect outbreaks (Cannon ; Logan et al ., ; Gregory et al ., ; Björkman et al ., ). Documented responses of insect pest populations to climate change vary widely (Johnson et al ., ; Haynes et al ., ; Ouyang et al ., ), however, ostensibly due in part to differences in life history and physiology (Walter et al ., ). Identifying which environmental variables drive population fluctuations, and how, is a first step towards predicting pest outbreaks in a changing climate.…”
Section: Introductionmentioning
confidence: 97%
“…In the US, declines have been 76 documented in populations of several wild bee species, butterflies in Ohio and lowland 77 California, and the migratory monarch butterfly (12)(13)(14)(15), while beekeepers sustain losses of > 78 40% of their managed honey bee colonies annually (16). There is also evidence that populations 79 of some insect pests are declining (17,18). 80…”
Section: Significance Statement 49mentioning
confidence: 99%